Pengaruh Lingkungan Kerja Dan Fasilitas Kerja Terhadap Kinerja Pegawai Pada Kantor Dewan Perwakilan Rakyat Daerah (DPRD) Provinsi Sumatera Barat - Rony Pangadilan; Alfian Alfian (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The analysis of this research is whether the work environment and work facilities have an effecthas a positive and significant effect on employee performance at the Representative Council OfficeRegional People of West Sumatra Province. The method that I use in this research isquantitative method with the help of the SPSS 22.0 program. This study uses analysismultiple linear regression. The population in this study were all House of Representatives employeesRegional People of West Sumatra Province, and Sample A total of 89 respondents. primary datausing the Questionnaire. This study shows that the work environment has a positive effectand significant to the performance of employees of the Regional Representatives Council of Sumatra ProvinceWest. tested and acceptable based on the t-count value of Variable X1 3.258 t-table 1.663 andsign value (0.002 < 0.005) The magnitude of the influence of the work environment (X1) on performanceemployees (Y) of 0.191 units. Work facilities have a positive effect on employee performance.tested and acceptable based on t-count (5.480) t-table (1.663) and sign (0.00) < 0.05.the magnitude of the influence of work facilities (X2) on performance (Y) is 0.445. which meanevery time there is a good work facility it will increase performance by 0.445 units. R² valueis 0.467 which indicates that the independent variable (X1,X2) explains the effectto the dependent variable namely Employee Performance of 0.467 or 46.7%. conclusion onIn this study, the work environment and work facilities have a positive and significant effecton the performance of employees at the Regional People's Representative Council office of Sumatra ProvinceWest.